Modelling and simulation of vaccine distribution: a COVID-19 situation. (25th April 2022) - Narassima, M.S.; Anbuudayasankar, S.P.; Balaji, K.S.; Ramasubramanian, B.
Ever since the onset of COVID-19, the healthcare fraternity and supply chains have faced severe disruptions like never before in the near past. The higher transmission rate of the virus has spread it worldwide. Vaccination is an inevitable phase to curtail the spread of the pandemic. The present study aims to develop an agent-based model to explain the distribution network of the vaccine. Grey relational analysis has been carried out to rank different states of India based on the critical variables that govern the transmission of the virus. This would help the policymakers rationally distribute the vaccines across different places. Further, sensitivity analysis has been performed with ten scenarios to compare the effects of positive and negative events, word of mouth, and the number of sessions on the distribution of vaccines. Increasing the sessions conducted per day from 163.33 by 40 and 80 increased the proportion vaccinated by 38.32 and 73.89 percentages, respectively.